Preliminary Study of Fear of Re-Injury following Sport-Related Concussion in High School Athletes. Issue 6 (18th August 2019) - Anderson, Melissa N.; Womble, Melissa N.; Mohler, Samantha A.; Said, Azkya; Stephenson-Brown, Katie; Kontos, Anthony P.; Elbin, RJ
ABSTRACT: The influence of fear of re-injury that this variable has on recovery outcomes following sports-related concussion remains unknown. We examined changes in fear of re-injury throughout concussion recovery, and compared changes in neurocognitive, symptom, vestibular/ocular motor, and recovery time outcomes between concussed adolescent athletes who endorsed high and low fear of re-injury. Individuals with high fear of re-injury were more symptomatic and more likely to exhibit vestibular/ocular motor symptoms over clinical cutoffs than those with low fear of re-injury. Recovery time was not significantly different between the groups. These findings may help explain performance on more subjective concussion assessments.